Virtual Reality as a Tool in the Treatment of Claustrophobia - A Review - Iparraguirre-Villanueva, Orlando (2023)
Within the context of psychology, virtual reality (VR) is presented as a technological tool to address and treat the symptoms of claustrophobia. Claustrophobia is distinguished by a fear of small or enclosed environments, which can be a challenge for conventional treatments. This research work focused on conducting a detailed analysis of the existing literature on using VR as an alternative tool to treat claustrophobia symptoms. The research results indicated that treatment with VR technology may be effective in providing a controlled and safe way to expose patients to situations such as those they fear, allowing them to overcome their fears more effectively. This review article provides a comprehensive analysis of the use of VR to treat laustrophobia. A total of 384 manuscripts from different virtual databases were analyzed, from which 61 major articles were selected. The results showed that VR allows for treating different types of phobias such as Acrophobia, Agoraphobia, rachnophobia, claustrophobia, Fear of flying, Fear of public speaking and Fear of injections, achieving significant patient results. Studies have proven the effectiveness of VR in reducing the symptoms of claustrophobia, and it is anticipated that it will continue to be an important tool in the future.